Single Dose Study Assessing the Pharmacokinetic and Metabolic Profile of Alverine Citrate in Healthy Volunteers - Rizea-Savu, Simona; Duna, Simona Nicoleta; Sandulovici, Roxana Colette (Frontiers in Pharmacology, 2021)
Alverine citrate is a spasmolytic commonly prescribed in conditions such as irritable bowel syndrome, painful diverticular disease of the colon, and primary dysmenorrhea. While clinical efficacy data on alverine alone or in combination with simethicone is freely available, surprisingly little information regarding the pharmacokinetics and metabolism of alverine can be found in literature. The first HPLC-MS/MS analytical protocol for determination of alverine parent, 4-hydroxy alverine, N-desethyl alverine and 4-hydroxy alverine glucuronide in human plasma was developed and validated. The two validated methods were used for analyzing plasma samples collected during an open label, non-comparative, single dose, one-period, one-treatment, pharmacokinetic and metabolic profile study of Spasmonal® Forte 120 mg hard capsule, conducted in 12 fasting healthy male and female volunteers of Caucasian descent. The study confirmed previous suspicions that parent alverine is subject to high pharmacokinetic variability and also revealed that the metabolic process most susceptible to outlying performance in Caucasians is hydroxylation to the active metabolite 4-hydroxy alverine. Another interesting observation made is that alverine parent accounts for only 3%, whereas total 4-hydroxy alverine (free and conjugated) accounts for 94% of alverine-related moieties in circulation (based on comparisons of total exposure).